2017
DOI: 10.1007/s10882-017-9557-x
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study Examining the Effectiveness of the PEERS Program on Social Skills and Anxiety in Adolescents with Autism Spectrum Disorder

Abstract: The Program for the Evaluation of the Enrichment of Relational Skills (PEERS), a social skills intervention for high functioning adolescents with autism spectrum disorder (ASD), has been proven efficacious in randomized control trials. However, the effectiveness of the PEERS program in community settings has not been studied. The present small-scale pilot study examined the effectiveness of the PEERS program in a community setting. Five adolescents and their caregivers participated in the PEERS intervention. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 20 publications
1
13
0
Order By: Relevance
“…Moreover, the findings showed a higher post-intervention recognition of the negative emotion of sadness and higher post-intervention production of happiness, sadness, fear, and anger. Albeit the study limitation is related to sample size, this evidence is in line with previous studies (Pennisi et al, 2016 ; Hill et al, 2017 ; Kumazaki et al, 2017 ; Sartorato et al, 2017 ; Saleh et al, 2020 ) suggesting that intensive training that applies technological devices helps children in filling the gap.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Moreover, the findings showed a higher post-intervention recognition of the negative emotion of sadness and higher post-intervention production of happiness, sadness, fear, and anger. Albeit the study limitation is related to sample size, this evidence is in line with previous studies (Pennisi et al, 2016 ; Hill et al, 2017 ; Kumazaki et al, 2017 ; Sartorato et al, 2017 ; Saleh et al, 2020 ) suggesting that intensive training that applies technological devices helps children in filling the gap.…”
Section: Discussionsupporting
confidence: 89%
“…A huge amount of studies have already demonstrated that interventions applying technological devices have positive effects on the development of social functioning in individuals with an ASC (Liu et al, 2008 ; Diehl et al, 2012 ; Kim et al, 2013 ; Aresti-Bartolome and Garcia-Zapirain, 2014 ; Giannopulu et al, 2014 ; Laugeson et al, 2014 ; Peng et al, 2014 ; Vélez and Ferreiro, 2014 ; Pennisi et al, 2016 ; Hill et al, 2017 ; Kumazaki et al, 2017 ; Sartorato et al, 2017 ; Saleh et al, 2020 ). Most of the studies in this field adopted robots as social mediators (Diehl et al, 2012 ), playmates (Barakova et al, 2009 ), or as behavior-eliciting agents (Damianidou et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…This program, which focuses on skills related to making friends and maintaining good relationships (Laugeson and Frankel 2010), has demonstrated not only immediate treatment gains for adolescents with ASD without intellectual disabilities (Dolan et al 2016;Laugeson et al 2009Laugeson et al , 2012Shum et al 2018;Yoo et al 2014), but also long-term treatment effects, even 1 to 5 years following the intervention (Mandelberg et al 2014). In addition, although the PEERS intervention does not aim to reduce social anxiety, a previous study showed significant decreases in social anxiety symptoms as compared with the waitlist control group (Hill et al 2017;Schohl et al 2013). This finding is promising because adolescents may become more likely to interact with peers by learning social skills.…”
mentioning
confidence: 99%
“…In a previous review (Miller et al 2014), social skills group interventions were found to be effective in their countries of origin have also been tested in different countries and shown evidence for generalizability, even in different cultural contexts. PEERS was originally developed in the United States, and has been shown to be effective in multiple trials in North America (Dolan et al 2016;Hill et al 2017;Laugeson et al 2009Laugeson et al , 2012Gantman et al 2012;Schohl et al 2013;Laugeson et al , 2015. PEERS has also been tested within Asia.…”
mentioning
confidence: 99%
“…First, Gardner et al (2015), studied 20 adolescents with ADHD who attended a 14-week university-based clinic program with 90-minute PEERS ® sessions each week found improvement across several peer functioning domains, and reported that many participants initiated new friendships. Next, Hill et al (2017), conducted a community-based PEERS ® program with five middle and high-schoolers diagnosed with ASD and some with ADHD to look at both social skills and anxiety. Using pretest and posttest data, they found significant progress was made in the individuals’ understanding and implementation of social skills.…”
mentioning
confidence: 99%